Understanding Costs and Outcomes in Child Welfare Services : a Comprehensive Costing Approach to Managing Your Resources. - Holmes, Lisa (Child Welfare Outcomes., 2011)
Today's child welfare services operate under a limited supply of resources which are being stretched by economic cuts and an increasing number of referrals to children's social care. This book provides a comprehensive costing approach which examines how finite resources can be most effectively used to provide support to the most vulnerable children and their families. Drawing upon the latest research and data, it outlines a methodology which has been applied to a range of child welfare services. The methodology breaks services down into component parts, creating a 'unit cost' for each type of.